Case report: Hepatic epithelioid angiomyolipoma with elevated alpha-fetoprotein and a history of breast cancer - Zhang, Xiaowei; Chen, Jun; Huang, Bifei; Wang, Lihong (Frontiers in Surgery, 2022)
Background: Perivascular epithelioid cell tumors have specific histology and immunohistochemistry (IHC). Epithelioid angiomyolipomas, found in the liver, have particularly rare characteristics. These tumors are relatively small and lack clinical and imaging specificity, and thus easily misdiagnosed as other primary or metastatic tumors before operating. Due to the significant epithelioid morphology and atypia of hepatic epithelioid angiomyolipoma (HEAML), intraoperative frozen pathological diagnosis is also challenging. Case presentation: A 33-year-old female patient was admitted to our hospital for elevated alpha-fetoprotein (AFP) levels after a regular checkup following breast cancer surgery. Initially, the possibility of liver cancer was considered based on enhanced magnetic resonance imaging (MRI) and color Doppler ultrasound examinations. Blood tumor composition showed AFP levels to be 23.05 ng/mL. The patient underwent right hepatic tumor resection assisted by laparoscopy. During the intraoperative cryopathology consultation, hepatocellular carcinoma was considered the likely diagnosis; however, postoperative pathology confirmed a right HEAML. The patient underwent regular checkups, for 23 months, without recurrence or distant metastasis. Conclusion: HEAML is easily misdiagnosed on preoperative imaging and intraoperative frozen pathological examination; medical professionals have to be aware of this possibility and proceed with caution. Postoperative pathological examination with a group of IHC markers is very helpful in diagnosing HEAML. The biological behavior of HEAML can be defined with low malignant potential. Surgical resection is the main treatment, and most patients have a good prognosis.